Molecular evidence to the day length in regulating the short shoot phenomenon during summer in roses (Rosa sp.). Issue 1 (31st December 2022) - Wang, Li; Jiang, Wan; Zhang, Wuhua; Chen, Weitong; Mo, Yu; Zhou, Tong; Zhang, Jinzhu; Che, Daidi
ABSTRACT: The short shoot phenomenon is an important phenotype underlying the economic value of roses – node number can directly affect shoot length. To elucidate the molecular mechanism of how day length affects shoot length, the effect of 8, 10, and 12 h day lengths on node number were studied. The number of nodes between the 8 and 12 h treatment groups significantly differed. Node development in the 12 h treatment group occurred significantly earlier than that in the 8 and 10 h treatment groups and the number of nodes reached a maximum on the third day. Using RNA-seq analysis, we identified candidate genes that regulated shoot length; these were involved in the abscisic acid synthesis pathway and auxin signal transduction and synthesis pathways. Furthermore, the abscisic acid content in the shoot tip decreased with an increasing day length, while the auxin content increased with day length.